Raw Cow Milk Thermostability and Its Relations to Other Indicators - Oto Hanuš; Eva Samková; Gustav Chládek; Marcela Klimešová; Petr Roubal; Irena Němečková; Radoslava Jedelská; Jaroslav Kopecký (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2018)
The aim was to evaluate the chosen relationships among milk composition, factors of primary milk production and milk thermostability (TES) on large data file during whole season (n 2,829). The results showed the TES mean 20.71 ± 8.19 minutes (geometric mean 19, median 20 minutes), from 3 to 57 minutes. Variation coefficient was 39.6%. The highest monthly mean was in September (23.98 ± 7.97, vx 33.3 % and xg 22.4 min.) and the lowest in January (16.5 ± 7.17, vx 43.5 % and xg 15.1 min.) and monthly mean values fluctuated (P 0.05). The surprising results are probably due to the lower variability and especially TCM, COLI and SCC level (248 ± 139 103ml-1; xg 218; vx 56.2 %; n 3,253) in the bulk milk. Significant effect on the TES was identified also in farms (P < 0.001). The results should contribute to an effective method of raw milk selection for dairy products with higher thermal stress during processing. The proposed selection limits for farms according to their history to predict better TES of raw material for 2 years of milk collection are: summer, TES mean over 17.5 minutes, variability up to 36.4 %; winter, over 13.0 minutes and up to 43.3 %.